2019
DOI: 10.1186/s13017-018-0221-2
|View full text |Cite
|
Sign up to set email alerts
|

Is early appendectomy in adults diagnosed with acute appendicitis mandatory? A prospective study

Abstract: IntroductionPrompt appendectomy has long been the standard of care for acute appendicitis in order to prevent complications such as perforation, abscess formation, and diffuse purulent or fecal peritonitis, all resulting in increased morbidity and even mortality. Our study was designed to examine whether the time from the beginning of symptoms to operation correlates with the pathological degree of appendicitis, incidence of postoperative complications, or increased length of hospital stay.MethodsA prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…No significant difference was found in length of hospital stay between the two groups (surgical: median 2 [IQR 2-3], conservative: median 3 [IQR 2-4]). WCC (surgical: median 15.9 [IQR 12.2-17.4], conservative: median 12.5 [IQR 10.4-15.6]) and Alvarado score (surgical: median 8 [IQR6-9], conservative: median 6 [ 5 - 8 ]) on admission was significantly higher in the surgical group compared to the conservatively managed group (p=0.012 and p=0.028, respectively). A summary of all patients having complications within six-month follow-up in both groups is provided in Table 3 , including imaging undertaken and initial WCC and Alvarado score.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No significant difference was found in length of hospital stay between the two groups (surgical: median 2 [IQR 2-3], conservative: median 3 [IQR 2-4]). WCC (surgical: median 15.9 [IQR 12.2-17.4], conservative: median 12.5 [IQR 10.4-15.6]) and Alvarado score (surgical: median 8 [IQR6-9], conservative: median 6 [ 5 - 8 ]) on admission was significantly higher in the surgical group compared to the conservatively managed group (p=0.012 and p=0.028, respectively). A summary of all patients having complications within six-month follow-up in both groups is provided in Table 3 , including imaging undertaken and initial WCC and Alvarado score.…”
Section: Resultsmentioning
confidence: 99%
“…The procedure has become routine and is associated with a significantly low mortality [ 4 ]. Early appendicectomy is recommended to avoid serious complications of appendicitis such as perforation, abscess formation and faecal peritonitis [ 5 ]. However, as with any surgical intervention, appendicectomy still involves significant risks [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…As noted in retrospective studies, acute appendicitis is a time-dependent disease concerning severity and complication rate [ 18 , 19 ]. On the other hand, some studies suggest that perforation is most often a prehospital occurrence and not strictly a time-dependent phenomenon [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, in adults, appendectomy remains the most effective and safe treatment option and provides curative treatment without risk. As noted in retrospective studies, acute appendicitis is a time-dependent disease concerning severity and complication rate [18,19]. On the other hand, some studies suggest that perforation is most often a prehospital occurrence and not strictly a time-dependent phenomenon [20].…”
Section: Resultsmentioning
confidence: 99%
“…A study by James et al reported that 27.8% of people in Milne Bay Province (PNG) did not have access to emergency surgery within two hours [10]. Such delay in presentation increases the risk of developing perforated appendicitis, sepsis and death [11][12][13]. The role of primary health care (PHC) thus becomes paramount in such a resource-limited setting.…”
Section: Introduction Backgroundmentioning
confidence: 99%